Professional role and identity of Icelandic preschool teachers : effects of stakeholders’ views - Arna H. Jónsdóttir 1953-; Coleman, Marianne (Early Years, 2014)
In this article, we explore the reality of Icelandic preschool teachers who are, as in most other countries, predominantly female. The gendered nature of the role and the current identity adopted by preschool teachers appear to impact on their perceived status and professionalism. In this process, stakeholders in early childhood education (ECE), as well as the preschool teachers themselves, play important parts. The question that underlies the paper is: ‘How do the views of preschool teachers and stakeholders in ECE affect the preschool teachers’ professional identity?’ The data used to answer the question are from focus group research carried out with preschool teachers and stakeholders in ECE in one community in Iceland. These stakeholders, besides preschool teachers and staff within the preschools, were parents, professionals at the municipal preschool office and politicians. The theoretical perspective informing the methodology of the research was ‘symbolic interactionism’ and the concept of ‘democratic professionalism’ was used as an aspirational framework to analyse the data. The findings reveal connections between the ideology relating to the preschool teachers’ educational role, their limited leadership and the gendered views of stakeholders. At the end of the paper, implications and recommendations for preschool teachers are suggested.